Human Rights, Business and the Investment Ombudsman of the Philippines - Santiago, III, Eugenio (Journal of Leadership, Accountability and Ethics, 2024)
Human rights and business are crucial elements in the development of the Philippine economy. The constitution safeguards the rights of both juridical and natural persons, including business owners and employees who play vital roles in economic progress for the welfare of all citizens. Businesses aim to generate profits, create jobs, and enrich investors through the utilization of labor and resources. However, unregulated operations can lead to resource exploitation, harming other stakeholders like labor, government, environment, and customers. The Office of the Ombudsman serves as the protector of legal rights for these entities. This paper explores the interplay between human rights, business, and the Investment Ombudsman in the Philippines. It delves into discussions on UN Business and Human Rights concepts, addressing political challenges, governance practices, stakeholder recommendations, and the Investment Ombudsman's role. This research can guide those interested in studying governance, business, and human rights integration, promoting sustainable development for the benefit of society.